2012
DOI: 10.1186/1550-2783-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes and food intakes of elite adolescent female figure skaters: a cross sectional study

Abstract: BackgroundElite adolescent female figure skaters compete in an aesthetic-based sport that values thin builds and lithe figures. To conform to the sport’s physical requirements, skaters may alter their eating patterns in unhealthful directions. This study assesses the eating attitudes and dietary intakes of elite adolescent female figure skaters to assess the potential nutritional risks among them.MethodsThirty-six elite competitive adolescent female figure skaters (mean age 16 ± 2.5 SD years) completed self-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
15
1
2
Order By: Relevance
“…Boa parte dos estudos realizados com jovens atletas apresenta resultados que evidenciam um padrão alimentar inadequado e com ingestão energética insuficiente, principalmente quando envolvidos em modalidades relacionadas a um maior controle da massa corporal (31,32) . Entretanto, outros trabalhos trazem resultados distintos, como balanço energético positivo identificado na alimentação de jovens lutadores (33) e em 45% da amostra de tenistas adolescentes (11) .…”
Section: Discussionunclassified
“…Boa parte dos estudos realizados com jovens atletas apresenta resultados que evidenciam um padrão alimentar inadequado e com ingestão energética insuficiente, principalmente quando envolvidos em modalidades relacionadas a um maior controle da massa corporal (31,32) . Entretanto, outros trabalhos trazem resultados distintos, como balanço energético positivo identificado na alimentação de jovens lutadores (33) e em 45% da amostra de tenistas adolescentes (11) .…”
Section: Discussionunclassified
“…2 Kulliyyah of Allied Health Sciences, International Islamic University, Malaysia. 3 National Sport Institute, Malaysia. 4…”
Section: Fundingmentioning
confidence: 99%
“…When athletes do not follow these recommendations, their performance may be affected. Several crosssectional studies on athletes' dietary intake found that most of them did not meet their energy requirements during training and competition (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended that the energy requirement for active Malaysian females aged between 19 and 29 years old is 2065 kcal/day (NCCFN 2005). However, it was found that female athletes reported energy intake of less than 2000 kcal/day (Dwyer et al 2012;Papadopoulou et al 2012;Shriver et al 2013) which substantially could not support their strenuous activity and nutritional demands (Reed et al 2014). Inadequate energy intake could reduce body weight and body fat of female athletes (Hall et al 2012) leading to reduction of reproductive hormonal secretion especially estrogen which negatively affect bone health (Quah et al 2009;Rauh et al 2010).…”
Section: Introductionmentioning
confidence: 99%